Illegal Fishing dalam Kajian Hukum Nasional dan Hukum Internasional: Kaitannya dengan Kejahatan Transnasional - Banjarani, Desia Rakhma (Kertha Patrika; Vol 42 No 2 (2020)DO - 10.24843/KP.2020.v42.i02.p04, 2020)
Illegal fishing practices are transnational in nature, which are not so easy to prevent and eradicate without international cooperation. Several international treaties both in the field of international maritime and fisheries law as well as international crimes have not categorized it as a transnational crime. This article discusses regulations that cover the issue of illegal fishing according to Indonesian national law and international law and examines the urgency of countermeasuring illegal fishing as a transnational crime. This article is a normative legal research with a statutory approach that explores the relevant national and international legal instruments which analyzed using descriptive methods. The results indicated that illegal fishing has been strictly regulated both in national and international law, although international law has not categorized illegal fishing as a crime that has cross-border characteristics. Therefore, there is an urgency to countermeasuring illegal fishing through international cooperation. In terms of the implementation of Indonesian national law, until now there seems to be lack of coordination between the national government and regional governments in establishing a mechanism related to efforts to prevent and eradicate illegal ?shing.   Praktik Illegal fishing bersifat transnasional yang sulit untuk dicegah dan diberantas tanpa adanya kerjasama internasional. Sejumlah perjanjian internasional baik di bidang hukum laut dan perikanan internasional maupun pidana internasional belum mengategorikan illegal fishing sebagai suatu kejahatan transnasional. Artikel ini membahas pengaturan terkait Illegal Fishing menurut hukum nasional Indonesia dan hukum internasional serta menelaah urgensi penanggulangan Illegal Fishing sebagai kejahatan transnasional.Artikel ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan yang menelusuri instrumen hukum nasional dan internasional yang relevan yang dianalisis dengan metode deskriptif. Hasil penelitian menunjukkan bahwa Illegal Fishing sudah diatur secara tegas baik dalam hukum nasional maupun hukum internasional, kendatipun kukum internasional belum mengategorikan illegal ?shing sebagai kejahatan yang memiliki karakteristik lintas batas Negara. Oleh karenanya, penanggulangan illegal fishing urgen dilakukan melalui kerjasama internasional. Dari segi implementasi hukum nasional Indonesia,hingga saat ininampaknya belum terdapat koordinasi antara pemerintah pusat dengan pemerintah daerah dalam menetapkan suatu mekanisme berkaitan dengan upaya pencegahan dan pemberantasan illegal ?shing.